Use of alternative medicine, ginger and licorice among Danish pregnant women - a prospective cohort study - Tabia Volqvartz; Anna Louise Vestergaard; Sissel Kramer Aagaard; Mette Findal Andreasen; Iana Lesnikova; Niels Uldbjerg; Agnete Larsen; Pinar Bor (BMC, 2019)
Abstract Background The use of alternative medicines and dietary supplements is constantly changing, as are dietary habits. One example of this phenomenon is the current popularity of ginger products as an everyday health boost. Ginger and licorice has also been shown to ameliorate nausea a common complaint in early pregnancy. Alternative medicines are often regarded as safe. However, they might affect fetal development, such as through alterations of hormone metabolism and cytochrome P450 function. Health care professionals may be unaware of the supplementation habits of pregnant women, which may allow adverse exposures to go unnoticed, especially if the rates of use in pregnancy are not known. We therefore investigated the use of alternative medicines and licorice among pregnant Danish women. Methods A total of 225 pregnant women were included in a prospective cohort when attending the national prenatal screening program at gestational weeks 10-16. Participants were asked to complete a questionnaire regarding their socio-economic status and lifestyle habits, including their intake of alternative medicine and licorice. Results We found that 22.7% of women reported taking alternative medicines, with 14.7% reporting daily consumption. Ginger supplements were consumed by 11.1%, mainly as health boost and 87.1% reported consumption of licorice. Regular or daily licorice consumption was reported by 38.2 and 7.1%, respectively. Notably, the use of licorice was reflected by an increase in blood pressure of the pregnant women. Conclusions The use of licorice and alternative medicines appears to be common in pregnant Danish women, supporting the need for further investigations into the safety of alternative medicine use during pregnancy and the importance of up-to-date personalized counseling regarding popular health trends and lifestyle habits.